2011
DOI: 10.1007/s10384-011-0071-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the anterior ocular segment measurements using swept-source optical coherent tomography and a scanning peripheral anterior chamber depth analyzer

Abstract: Based on our results, the SS-OCT and SPAC measurements of the anterior segment were significantly correlated, but the values cannot be considered to be directly interchangeable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Because it is easy to obtain it, there exist dedicated methods of image analysis and processing capable of performing this type of measurement fully automatically [38]. The methods proposed and implemented by tomographs' manufacturers work properly even for patients with a high degree of pathology or for large interindividual variability.…”
Section: Comparison With Other Authors' Resultsmentioning
confidence: 99%
“…Because it is easy to obtain it, there exist dedicated methods of image analysis and processing capable of performing this type of measurement fully automatically [38]. The methods proposed and implemented by tomographs' manufacturers work properly even for patients with a high degree of pathology or for large interindividual variability.…”
Section: Comparison With Other Authors' Resultsmentioning
confidence: 99%
“…Due to recent advancements in hardware and software, technologies including the SS system and multiple scan averaging that were developed in posterior segment OCT have been incorporated in anterior segment OCT systems, achieving high-speed, high-quality, and high-penetration imaging. [21][22][23][24][25][26][27] In this study, en face OCT imaging, which has also been used in retinal and choroidal diseases, was applied for visualization of the vasculature, 28,29 whereas previous studies reported B-scanbased vessel image construction. 30,31 Combined with the flattening technique, the use of the en face video and its projection (vasculature map) revealed a clear blood stream that was not depicted by a sequential stack of B-scans.…”
Section: Discussionmentioning
confidence: 99%
“…The two graders agreed on their evaluations of study parameters. The instrument software in the SS-1000 Casia instrument analyzed the following parameters: anterior chamber depth (ACD; mm), anterior chamber volume (ACV; mm 3 ), ACA (angle opening distance [AOD750; mm] and trabecular iris space area [TISA750; mm 2 ]), iris thickness (IT; mm), iris volume (IV; mm 3 ), and iris curvature (IC; mm) [11]. The AOD750 was defined as the distance from the corneal endothelium to the anterior iris surface, perpendicular to a line drawn 750  μ m anterior to the scleral spur.…”
Section: Methodsmentioning
confidence: 99%